Preface - WIĘCKOWSKI, Dariusz (Engineering Transactions, 2025)
Preface to a selection of papers presented at the SiMRTRANS Scientific and Technical Conference: “Innovative Solutions in Transport”, which took place at the Warsaw University of Technology, Faculty of Automotive and Construction Machinery Engineering, on September 19, 2024.